Pro DNS and BIND - Aitchison, Ron (Expert's voice in open source., 2005)
Pro DNS and BIND guides you through the challenging array of features surrounding DNS, with a special focus on BIND, the world's most popular DNS implementation. This book unravels the mysteries of DNS, offering insight into origins, evolution, and key concepts like domain names and zone files. This book focuses on running DNS systems based on BIND 9.3.0 the first stable release that includes support for the latest DNSSEC (DNSSEC.bis) standards and a major functional upgrade from previous BIND 9 releases. If you administer a DNS system or are thinking about running one, or if you need to upgrade to support IPv6 DNS, need to secure a DNS for zone transfer, dynamic update, or other reasons, or if you need to implement DNSSEC, or simply want to understand the DNS system, then this book provides you with a single point of reference. Pro DNS and BIND starts with simple concepts, then moves on to full security-aware DNSSEC configurations. Various features, parameters, and resource records are described and, in the majority of cases, illustrated with one or more examples. The book contains a complete reference to zone files, Resource Records, and BINDs configuration file parameters. You can treat the book as as a simple paint-by-numbers guide to everything from a simple caching DNS, to the most complex secure DNS (DNSSEC) implementation. Background information is still included for when you need to know what to do and why you have to do it, and so that you can modify processes to meet your unique needs.